Polarographic Study of Some Arylidene-2-Pyridylhydrazones - Mohammed A. Al-Nuri; Mohammed A. Hannoun; Jamal S. Shalabi (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The polarographic behaviors of some arylidene-2-pyridyl hydrazones have been studied in aqueous Britton - Robinson buffer solution containing 40% ethanol using DC polarographic technique. In the pH range 1.9 - 6.4 the observed single irreversible 4 - electron reduction wave is attributed to the splitting of the N - N bond and saturation of C = N centre. All compounds studied are polarographically inactive in alkaline medium. The effect of pH on the limiting current and E 112 as well as the reduction mechanism and the effect of substituent's are discussed and compared with similar compounds. The kinetic parameters of the electrode reaction have been calculated.